Efavirenz and rifampicin in the South African context: is there a need to dose increase efavirenz with concurrent rifampicin therapy? - Orrell, Catherine (2011)
INTRODUCTION: Increasing EFV dose from 600mg to 800mg daily has been suggested with concomitant RFN, as induction of cytochrome p450 isoenzymes may reduce EFV plasma concentrations METHODS: Individuals from the CIPRA-South Africa cohort taking EFV-based ART with concomitant TB were dosed with either increased-(800mg) or standard-(600mg) dose EFV during TB treatment. After TB therapy all took 600mg EFV. Two mid-dosing interval EFV concentrations were determined from each individual: after 4 weeks of concomitant EFV and RFN therapy, and at least 4 weeks after TB therapy completion. Mid-dosing interval EFV concentrations were compared within individuals using the Wilcoxon signed rank test. RESULTS: Paired-samples were collected from 72 individuals. 45(63%) were women; median weight 59kg (IQR52-67kg). At ART start median CD4 count was114 cells/mm3 (IQR37-165), median viral load 5.5log (IQR5.1–5.9). 38 (53%) took 800mg EFV during TB treatment and 34(47%) took 600mg. EFV concentrations in the 800mg group were higher with RFN [[2.9mg/L (IQR 1.8–5.6)] than without [2.1mg/L (IQR 1.4–3.0)]], p=0.0003. There was no significant difference in EFV concentrations with RFN [2.4mg/L (IQR1.2–5.1)] or without [2.2 mg/L (IQR 1.4 to 3.7)] in the 600mg group. There was no increase in EFV-linked adverse effects in either group. Proportion virologically suppressed at 48 weeks was similar in both groups. CONCLUSION: EFV concentrations were significantly increased in the EFV 800mg group on RFN. There was no significant decrease in EFV concentrations when on RFN in the 600mg group. Dose escalation of EFV 600mg to 800mg is not required during concomitant TB therapy in South Africa.